Aortic valve-sparing root replacement in patients with bicuspid aortic valve: long-term outcome with the David I procedure over 20 years. (3rd April 2020) - Beckmann, Erik; Martens, Andreas; Krüger, Heike; Korte, Wilhelm; Kaufeld, Tim; Stettinger, Alissa; Haverich, Axel; Shrestha, Malakh Lal
Abstract: OBJECTIVES: Aortic valve-sparing root replacement is an excellent treatment option for patients with intact tricuspid aortic valves. However, the durability in patients with bicuspid aortic valves is still a matter of debate. The aim of this study was to analyse the short- and long-term outcomes in patients with bicuspid aortic valves. METHODS: Between July 1993 and October 2015, a total of 582 patients underwent the David I procedure, 50 of whom had a bicuspid aortic valve. In these patients, the mean age was 46 ± 13 years, and 80% ( n  = 40) were men. Follow-up was complete for 100% of patients and comprised a total of 552 patient-years with a mean follow-up time of 11 ± 5.2 years. RESULTS: In addition to the David procedure, cusp plication was performed in 34% ( n  = 17) of patients and commissure repair in 8% ( n  = 4) of patients. There were no in-hospital deaths, and 1 patient (2%) had a perioperative stroke. The 1-, 5-, 10- and 20-year survival rates of patients after discharge were 98%, 94%, 88% and 84%, respectively. The rates for freedom from valve-related reoperation at 1, 5, 10 and 20 years after initial surgery were 98%, 88%, 79% and 74%, respectively. Long-term freedom from reoperation was comparable to that of patients with tricuspid aortic valves ( P  = 0.2). CONCLUSIONS: The David procedure has excellent short-term results in patients with a bicuspid aortic valve. In this study, the long-term durability of reimplanted bicuspid aortic valves was comparable to that of tricuspid valves. However, careful patient selection might have contributed to this, and further studies might be needed to definitely clarify this issue.